The World Federation of Societies of Biological Psychiatry guidelines on the assessment and pharmacological treatment of compulsive sexual behaviour disorder - Turner, Daniel; Briken, Peer; Grubbs, Joshua; Malandain, Leo; Mestre-Bach, Gemma; Potenza, Marc N.; Thibaut, Florence (Dialogues in Clinical Neuroscience, 2023)
Objectives: The current guidelines aim to evaluate the role of pharmacological agents in the treatment of patients with compulsive sexual behaviour disorder (CSBD). They are intended for use in clinical practice by clinicians who treat patients with CSBD. Methods: An extensive literature search was conducted using the English-language-literature indexed on PubMed and Google Scholar without time limit, supplemented by other sources, including published reviews. Results: Each treatment recommendation was evaluated with respect to the strength of evidence for its efficacy, safety, tolerability, and feasibility. Psychoeducation and psychotherapy are first-choice treatments and should always be conducted. The type of medication recommended depended mainly on the intensity of CSBD and comorbid sexual and psychiatric disorders. There are few randomised controlled trials. Although no medications carry formal indications for CSBD, selective-serotonin-reuptake-inhibitors and naltrexone currently constitute the most relevant pharmacological treatments for the treatment of CSBD. In cases of CSBD with comorbid paraphilic disorders, hormonal agents may be indicated, and one should refer to previously published guidelines on the treatment of adults with paraphilic disorders. Specific recommendations are also proposed in case of chemsex behaviour associated with CSBD. Conclusions: An algorithm is proposed with different levels of treatment for different categories of patients with CSBD.
Keywords: compulsive sexual behaviour disorder; hypersexuality; addictive behaviours; compulsive behaviours; sexual addiction; paraphilias; chemsex; JCR